Effects of Contact Sports on Temporomandibular Disorders: An Observational Study - Vito Crincoli; Corrado De Biase; Angela Pia Cazzolla; Alessandra Campobasso; Mario Dioguardi; Maria Grazia Piancino; Luigi Mattia; Domenico Ribatti; Mariasevera Di Comite (MDPI AG, 2022)
The study investigated the prevalence of temporomandibular disorders in 100 competitive athletes in contact sports, equally grouped by the practiced game: Soccer (SoG), Rugby (RG), American Football (AFG), Boxing (BoG), Basketball (BaG), compared to a randomly control group of 20 non-athletes (CG). Symptoms and signs were examined according to the standardized Diagnostic Criteria for Temporomandibular Disorders through a questionnaire and clinical evaluation. Arthralgia showed significant differences between RG and CG and between AFG and CG (p < 0.05). Study groups reported masticatory muscle pain during function, neck and shoulder pain more frequently than CG, except for BoG. Closing click was significantly more present in study groups than CG, while crepitation was significantly higher only in RG and AFG. The deviation was wider in SoG, RG and AFG compared to CG (p < 0.05). Tukey's multiple comparisons test showed a statistically significant reduction in right laterotrusion in RG vs. CG (p < 0.05); the comparison showed a decrease in right laterotrusion in RG vs. SoG and BoG (p < 0.05), a decrease in endfeel in RG vs. CG, BaG and AFG (p < 0.05). The data seem to support a relationship between the prevalence of TMD symptoms and signs in competitive athletes in contact sports, especially in RG and AFG compared to CG.